Efficiency evaluation of filters in fan coil classrooms for particle reduction from haze - Wu, Hongqing (2016)
Experiments were performed to investigate how filters could help to improve indoor air quality during non-occupancy period in small spaces, also, the composition of PM2.5 after entering indoor. Locations of the experiment were classrooms in Nanyang Technological University campus. Filters range from 25% to 95% efficiency (i.e. MERV6 ~ MERV14) were attached on return and extract grille of fan coil unit system. Optical Particle Counter and Optical Particle Sizer measured particle concentration in 5 classrooms with different filter grades. Records were divided into 6 bins of particle size range, which the cut points are 0.3μm, 0.5μm, 1.0μm, 2.5μm, 5.0μm and 10.0μm. Performance of filter were evaluated based on ANOVA test by comparing efficiency provided by the effect of air-conditioning and attached filter, as well as I/O ratio. In addition, composition of PM2.5, which contained first 3 bins, were analysed. Results indicated that 95% filter would be better if solely considering the effect of air-conditioning and attached filters. However, 85% filter would be better if evaluating the overall improvement of air quality indoor and economic factor. For composition of PM2.5, particles ranged 0.3~0.5μm contributed most portion in PM2.5 during days with moderate and unhealthy PSI indoor and outdoor. 0.5~1.0μm particles took up most portion during day(s) with very unhealthy PSI at outdoor environment. Limitation of this project is that efficiency evaluation of filters during heavy haze was lack of data. Only two days’ air quality were within very unhealthy range, while the other days were within moderate to unhealthy range.